Seronegative myasthenia gravis. - Vincent, A; McConville, J; Farrugia, M; Newsom-Davis, J (2004)
Some myasthenia gravis (MG) patients do not have detectable acetylcholine receptor (AChR) antibodies and have been termed "seronegative" (SNMG) in many previous studies. A high proportion of patients with purely ocular symptoms, ocular MG, are seronegative; this may be because the sensitivity of the assay is insufficient to detect low levels of circulating AChR antibodies and because of intrinsic differences in the ocular muscles that make them more susceptible to circulating factors. Seronegative generalized myasthenia is proving to be heterogeneous both clinically and immunologically. Plasma from SNMG patients often contains a factor, probably an immunoglobulin M antibody, that alters AChR function in in vitro assays, but its target is not yet clear. A variable proportion of SNMG patients have antibodies to the muscle-specific tyrosine kinase (MuSK). These antibodies are directed against the extracellular domain of MuSK and inhibit agrin-induced AChR clustering in muscle myotubes. Although the role of these antibodies in causing myasthenic symptoms in vivo has not been elucidated, MuSK antibodies appear to define a group of patients who are often female with bulbar weakness, contrasting with MuSK antibody-negative SNMG patients who are more likely to have generalized weakness. MuSK antibody-positive patients may also differ in the distribution of their electrophysiological abnormalities and their responses to treatments.